Developing an effective teaching model in order to improve the educational level of schools - Mehdi Mohammadi; fardin Abdollahy; Rafigh Hasani (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research was to develop an effective teaching model in order to improve the educational level of schools. This research is qualitative and phenomenological. The research community includes academic experts familiar with the subject. Based on the purposeful sampling method; after a semi-structured interview with 15 people, theoretical saturation was achieved and the interview was stopped. In this research, consultants and experts in the field of educational management were used to achieve validity, and the verification strategy of research colleagues was used to determine reliability; based on this, validity and reliability were confirmed. The method of analysis used in this research was thematic method. Based on the results of the interviews, 11 themes in the form of 4 concepts of personal and scientific characteristics of teachers (social status of teachers, individual character of teachers, and empowerment of teachers), optimal management of the classroom and educational environment (use of educational technology, classroom management and effective educational implementation, and appropriate educational tools and equipment), active and motivating teaching (use of active teaching methods and motivational levers), and targeted teaching (objectification of teaching (meaningful learning), targeted research) were identified. Based on this, it is suggested to use the model presented in this research in order to improve the educational level of schools and make teachers' teaching more effective.Extended abstractIntroductionAmong all the duties of education, teaching can be considered one of the basic duties that have an interactive relationship with other duties; and in fact, it can be considered as the foundation of other duties of education. Considering the importance of teaching and the role of its infrastructure in achieving educational goals in theoretical and practical fields, emphasizing effective teaching in a way that can provide the achievement of important goals is a certain and obvious thing (Mohammadi Khangah & Hosseinzadeh, 2015). Teaching is a comprehensive, multiple, complex phenomenon in which the role of the teacher and learners has changed (Mahdian & Amini, 2018). In fact, teaching includes a set of skills that take place before, during and after the implementation of the teaching process, and provide the possibility of teaching students (Devlin & Samarawickrema, 2022). Today, traditional educational methods are no longer suitable and effective for the current society (Mehrabiniya et al, 2022). The effectiveness of teachers' teaching in the classroom consists of various dimensions, including: respect for students, the ability to challenge and stimulate their minds, lesson organization, speech skills, and presentation of materials in an appropriate manner (Aldrup, Carstensen et al, 2022). The meaning of effective teaching is a set of teacher's actions and characteristics that lead to the achievement of educational goals and students' learning (Wang & Cheng, 2023). The role of the education system in the growth and development of societies is outstanding and undeniable. However, one of the main problems in education is the lack of effective teaching indicators. Considering the importance of teaching and the role of its infrastructure in achieving educational goals in theoretical and practical fields, it is obvious to emphasize effective teaching in a way that can provide the achievement of important educational goals. Major changes are taking place in the educational system. Based on this, the main issue in this research is the answer to the question: what is the appropriate model of effective teaching in order to improve the educational level of schools?Theoretical frameworkOne of the duties of teachers in the process of education and training is to lay the groundwork for the growth and learning of students, and in modern education and training, the emphasis is on the activeness of the learner in the process of learning and the formation of mental construction (Fallahi & Rostami, 2012). Therefore, the activity that takes place in the teaching and learning process must have the characteristics to be called teaching. One of the prominent features of such an activity is that two people are involved in it and each of them is involved in a specific way (Eslamian, Ealamian & Karami, 2018). Wang and Cheng (2023) consider teaching to be an interactive and two-way process in which both the learner and the instructor are affected by each other, and teaching in this sense is the explicit expression of what needs to be learned. The most basic definition of effective teaching is the teacher's ability to help students and learners reach high standards (Hoseini hesam abadi et al, 2023). Effective teaching should be regular and stimulating, and promote motivation, vitality, innovation, and increase the efficiency of teachers and students (Bidabadi et al., 2016). Devlin & Samarawickrema (2022) showed that effective teaching criteria have changed after the Covid-19 pandemic and are more based on interactions between the teacher and students. Chew & Cerbin (2021) showed that effective teaching requires solving nine challenges, including changing the mental mindset of students, metacognition and self-regulation, student fear and distrust, prior knowledge, misconceptions, ineffective learning strategies, learning transfer, selective attention limitations and mind effort limitations, and active memory. Abedini et al, (2020) in a research found that 10 factors, including the teacher's mastery of the subject, the expression of clear educational expectations, the power of leadership and classroom management, the active participation of students in the teaching process are affecting factors in effective teaching. Shirbagi and Nasirinia (2020) in examining the professional development of a step towards effective teaching in Sanandaj elementary school teachers showed that the "characteristics of effective professional development" questionnaire has good validity and reliability for use among Iranian teachers. Among the components of effective professional development from the point of view of teachers, according to the results of the Friedman test, the first rank of these components was focusing on the content knowledge of teachers and how students learn the material, and the last rank was active learning beyond the classroom. Also, there is a significant difference between the components of effective professional development of teachers.MethodologyThis research is fundamental in terms of its purpose, and exploratory in terms of the method of data collection. The research has been conducted qualitatively. Considering that the purpose of this research is to identify the dimensions and components that influence effective teaching and formulating a model, and on the other hand, we tried to make the obtained results as realistic as possible; on this basis, a qualitative approach was used. Qualitative data was collected using library studies and semi-structured interviews. The statistical population of this research included academic experts familiar with the subject, and theoretical data saturation index was used to determine the sample size. In order to analyze the data, the theme analysis method was used.Research findingsIn order to examine and answer the research question, after collecting, arranging and organizing the codes resulting from each interview and based on the thematic method, key words and points in the form of an index was extracted from the interview text. For this purpose, the codes collected through interviews were collected and organized in a database. Based on the results of the interviews, 11 themes in the form of 4 concepts of teachers' personal and scientific characteristics (teachers' social status, teacher's individual personality and teachers' empowerment), optimal classroom management and educational environment (use of educational technology, classroom management and effective educational implementation, educational tools and equipment appropriate), active and motivating teaching (use of active teaching methods and motivational levers), and purposeful teaching (objectification of teaching (meaningful learning), targeted research) were identified.ConclusionThe purpose of this research was to develop an effective teaching model in order to improve the educational level of schools. The results of this research are consistent with the findings of Aldrup et al. (2022), Devlin & Samarawickrema (2022), and Chew & Cerbin (2021). In explaining the findings of this research, it can be said that the optimal classroom management mentioned by the interviewees includes: classroom preparation, planning, parents' participation in their children's education process, welcoming students' interaction with each other, the ability to communicate with problematic students, continuous and formative evaluation, respecting the order of the teacher while teaching, having a lesson plan, having a logical order in teaching, on time attendance control, strictness on time, removing communication barriers while teaching, providing a learning environment, and human relations governing the classroom atmosphere. Class management includes all the decisions and actions necessary to discipline the class and is brought up under the title of discipline. This type of order means managing, maintaining, or providing an environment in which proper learning is done along with reducing issues and problems for students. Also, effective teaching requires the use of appropriate educational tools and equipment. The facilities and physical space of the classroom, the use of multimedia in teaching, the use of lesson presentation software (PowerPoint and Parzi), creating a positive learning environment, using warm and soothing colors for the classroom, having workshops and laboratories for special courses are some of these tools and equipment. Finally, it is suggested that the school administrators help the teacher to improve the quality of teaching by providing a healthy atmosphere and adequate educational materials. Also, in future research, the effect of factors such as distributed leadership style, professional support, professional commitment, etc. on effective teaching based on the model identified in this research should be investigated. It is also suggested to use the model presented in this research in order to make the teaching process in schools more effective.